FUNGSI UU NOMOR 41 TAHUN 2004 TENTANG WAKAF DALAM MEMPERKOKOH EKSISTENSI DAN STATUS HUKUM WAKAF TUNAI - Agus Susanto (Universitas Siliwangi, 2019)
This article is aimed to describe the functions of the Operative Act Number 41 Year 2004 about Waqf (endowment) towards cash waqf and its effect on legal status of cash waqf. There are such reasons urged The Government to intervene this religious social institution until the Operative Act Number 41 Year 2004 about Waqf was declared. This legislation has many functions such as social control and social engineering; not only solve many existing problems of waqf but to create a change constructively in society. Moreover, the legislation also plays a regulatory function which arranging waqf properties, institutionalization, and management of waqf development. It has function else such as legitimacy toward any institutions made by government. When this Operative Act was declared, status of cash waqf—which was debatable—declare legally valid based on ijtihâd fî tathbîq al-ahkâm by using ijtihâd jama`iy method. Determination of legal status of cash waqf is considered important which is closely related to public legal awareness; so that it can be impetus for the development of cash waqf.